2021
DOI: 10.7759/cureus.18566
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Reference Levels for Common X-ray Procedures in Peru

Abstract: Diagnostic reference levels (DRLs) for X-ray procedures have been established in many countries since 1996. In Peru, data from the literature are used as guidelines as DRLs research is limited. The objective of this study is to analyze the parameters and variables which are used in radiological techniques such as kV, mAs, and type of machine (conventional or digital); study the geographical distribution of radiological X-ray machines, and establish DRLs in Peru. Two radiological procedures were considered, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…Comparison of the third quartile value of K a, i for the intraoral procedure, with the other countries' DRLs [ Table 3 ], reveals that the values obtained in this study are close to values obtained in studies in Japan[ 13 ] (1.51 mGy) and Germany[ 14 ] (1.5 mGy), and lower than values obtained in Cyprus[ 21 ] (4.75 mGy), Korea[ 22 ] (3.1 mGy), and Peru[ 23 ] (4.21 mGy). The vast use of fast-speed films and digital detectors may also have contributed to the lower DRLs in the present study.…”
Section: R Esults and Discussionsupporting
confidence: 79%
“…Comparison of the third quartile value of K a, i for the intraoral procedure, with the other countries' DRLs [ Table 3 ], reveals that the values obtained in this study are close to values obtained in studies in Japan[ 13 ] (1.51 mGy) and Germany[ 14 ] (1.5 mGy), and lower than values obtained in Cyprus[ 21 ] (4.75 mGy), Korea[ 22 ] (3.1 mGy), and Peru[ 23 ] (4.21 mGy). The vast use of fast-speed films and digital detectors may also have contributed to the lower DRLs in the present study.…”
Section: R Esults and Discussionsupporting
confidence: 79%
“…Incident air kerma (INAK) is the KAR obtained with the radiation detector at a distance of 20cm representing the phantom surface [11].…”
Section: Dose Assessmentmentioning
confidence: 99%
“…In the literature, no material was found that classifies a visual scale to validate the quality assessment of anteroposterior (AP) pelvic examinations, as mentioned in the article by Mraity HAAB et al Therefore, in this study, we quantitatively evaluated the quality using descriptors such as signal-to-noise ratio (SNR) and its relationships. The software ImageJ was employed to obtain these values through Regions Of Interest (ROI) analysis [11].…”
Section: Image Qualitymentioning
confidence: 99%
“…KERMA no ar incidente obtido com a câmara de ionização na distância de 20cm representando a superfície do fantoma e BSF é o fator retroespalhamento (do inglês backscatter factor). Utilizou-se o valor de 1,4, adequado para os valores de tensão do estudo, conforme o formalismo Arcal XLIX(PORTOCARRERO et al, 2021).A qualidade das imagens foi avaliada por meio de um software de domínio público, ImageJ(WAYNE, 2022). Para determinar entre as regiões de interesse (do inglês -regions of interest -ROI) o sinal e o ruído das imagens obtidas, foram posicionados na imagem 6 ROIs para cada técnica.O primeiro centralizado no Osso Sacro (S1), o segundo na Asa Ilíaca Direita, o terceiro na Asa Ilíaca…”
unclassified